Epstein-Barr Virus-Positive Leiomyosarcoma in Immunocompetent Patients - Hassan AL-TARAWNEH; Alpaslan ALP; Gokhan GEDIKOGLU; Kemal KOSEMEHMETOGLU (Federation of Turkish Pathology Societies, 2024)
Objective: Epstein-Barr Virus-Associated Smooth Muscle Tumor (EBV-SMT) is a rare tumor with a higher rate of occurrence in unusual locations in the setting of immunodeficiency. In this study, we evaluated a cohort of ordinary leiomyosarcomas (LMS) for the presence of EBV and described the clinicopathological features deviating from routinely diagnosed cases of EBV-SMT. Material and Method: The sections of tissue microarrays including 93 classical LMS occurring in various locations were hybridized with EBER and stained for LMP1 antibody using the Leica Bond Autostainer. EBV real-time PCR assay was performed in 2 EBER-positive cases. Results: Among the 93 LMS cases, 2 non-uterine cases (2.2%) were positive for EBER and negative for LMP1, and were referred to as `EBV-positive LMS`. Both were females in their 6th decade without immunosuppression. EBV real-time PCR assay revealed the presence of EBV in one of the cases. Tumors were located in the pancreas and chest wall. Morphologically, tumors were rather myxoid, multinodular, and composed of long fascicles of spindle cells with intermediate- to high-grade features. High mitotic activity and focal necrosis were present, whereas no accompanying lymphocytes were detected. One of the patients developed metastatic disease after 3 years. Conclusion: EBV-positive LMS occurring in immunocompetent patients has features distinct from classical EBV-SMT seen in immunosuppressed patients.